Rendition [videorecording (DVD)] - Hood, Gavin; Golin, Steve; Viscidi, Marcus; Sane, Kelley; Gyllenhaal, Jake, 1980-; Witherspoon, Reese, 1976-; Sarsgaard, Peter; Metwally, Omar; Naor, Yigal, 1958-; Khouas, Mohammed; Oukach, Zineb; Arkin, Alan; et al. (New Line Home Entertainment : Warner Home Video, 2008)
The policy of "extraordinary rendition" began under the Clinton administration and accelerated after September 11, 2001. The policy allows for the handing over of suspected terrorists to countries that use torture as an interrogation tool. Anwar El-Ibrahimi is an Egyptian-born man who disappears on a flight from Africa to Washington, DC. He is sent to a North African country where torture is practiced and the CIA gives approval. Anwar's pregnant American-born wife wants to know what happened to her husband. A reluctant CIA agent begins to question his assignment after witnessing an unorthodox interrogation. A severe interrogator plies his trade on Anwar while a U.S. terrorism honcho is willing to turn a blind eye to the unpleasantness, especially if it stops a terrorist attack